2011
DOI: 10.5194/acp-11-9771-2011
|View full text |Cite
|
Sign up to set email alerts
|

Cloud optical thickness and liquid water path – does the <i>k</i> coefficient vary with droplet concentration?

Abstract: Abstract. Cloud radiative transfer calculations in general circulation models involve a link between cloud microphysical and optical properties. Indeed, the liquid water content expresses as a function of the mean volume droplet radius, while the light extinction is a function of their mean surface radius. There is a small difference between these two parameters because of the droplet spectrum width. This issue has been addressed by introducing an empirical multiplying correction factor to the droplet concentr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
68
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 46 publications
12
68
1
Order By: Relevance
“…Results confirm that the CDSD is broadened during diffusional growth due to Ostwald ripening and associated droplet deactivation and reactivation, which is consistent with previous studies (e.g., Korolev, 1995;Çelik and Marwitz, 1999). In this study, we investigate (1) what are the relative roles of the solute and curvature effects on CDSD broadening, and (2) what other factors can affect this broadening?…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Results confirm that the CDSD is broadened during diffusional growth due to Ostwald ripening and associated droplet deactivation and reactivation, which is consistent with previous studies (e.g., Korolev, 1995;Çelik and Marwitz, 1999). In this study, we investigate (1) what are the relative roles of the solute and curvature effects on CDSD broadening, and (2) what other factors can affect this broadening?…”
supporting
confidence: 78%
“…Korolev (1995) argued that stronger turbulent fluctuations of supersaturation would result in a broader CDSD. This is contrary to Çelik and Marwitz (1999), who found that supersaturation fluctuations are not responsible for CDSD broadening and the formation of large droplets. The curvature and solute effects on Ostwald ripening, activation and deactivation have been topics of study in recent years (e.g., Wood et al, 2002;Arabas and Shima, 2017;Chen et al, 2018;Sardina et al, 2018) but, to our knowledge, the relative roles of the curvature effect and solute effect on CDSD broadening have not been investigated.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…Slingo 1990; Vilà-Guerau de Brenguier et al 2011;Lohou and Patton 2014). For a tropical shallow Cu case, as studied here, observational evidence shows that r e = 10 −5 m is an acceptable approximation of the modal droplet radius (McFarlane and Grabowski 2007;Brenguier et al 2011). This surface shading introduces two effects: firstly a domain-averaged decrease in surface fluxes, and secondly a surface heterogeneity because the actual decreases in surface fluxes are local.…”
Section: Design Of Numerical Experimentsmentioning
confidence: 99%
“…This is a widely used method for calculating τ (e.g. Slingo 1990; Vilà-Guerau de Brenguier et al 2011;Lohou and Patton 2014). For a tropical shallow Cu case, as studied here, observational evidence shows that r e = 10 −5 m is an acceptable approximation of the modal droplet radius (McFarlane and Grabowski 2007;Brenguier et al 2011).…”
Section: Design Of Numerical Experimentsmentioning
confidence: 99%